ANALISIS PENGEMBANGAN PUSAT PERTUMBUHAN EKONOMI DI KABUPATEN BANJARNEGARA - Refika Ardila (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2012)
The goals of this research are to find out which the sub-districts as the center of economy growth, to find out the interaction between the sub-district as the center of economy growth and the hinterland sub-district, to know the condition of the sub-district economy and the potential economic sectors in every sub-district in Banjarnegara Regency. The population of this research is the sub-district in Banjarnegara Regency. The method of accumulating data used are documentation and interview method. The analyses used are skalogram and centrality index analysis, gravity method, klassen typology analysis, and Location Quotient analysis. Based on the result of research, it is obtained six-districts which include the sub-district as the center of economic growth such as Madukara, Banjarnegara, Purwanegara, Mandiraja, Purwareja Klampok, and Susukan sub-district. The interaction and the number of interaction between the sub-district as the center and the hinterland sub-district is different. The majority of sub-districts are still in the relatively lagging area. The basis sectors spread evenly in the twentysub-districts in Banjarnegara, however the most dominant basis sector are the agricultural sector, the electricity sector, gas and clean water, the building sector and the services sector. The conclusion is the sub-district as the center of economy growth interacting each other with the surrounding sub-district. The economy condition and the basis sectorin every sub-district are different